2017
DOI: 10.1111/cobi.12878
|View full text |Cite
|
Sign up to set email alerts
|

Toward accurate and precise estimates of lion density

Abstract: Reliable estimates of animal density are fundamental to understanding ecological processes and population dynamics. Furthermore, their accuracy is vital to conservation because wildlife authorities rely on estimates to make decisions. However, it is notoriously difficult to accurately estimate density for wide-ranging carnivores that occur at low densities. In recent years, significant progress has been made in density estimation of Asian carnivores, but the methods have not been widely adapted to African carn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(116 citation statements)
references
References 46 publications
2
112
2
Order By: Relevance
“…Additionally, recent research has shown that lion numbers do not negatively influence cheetah numbers (Swanson et al., 2014), which is likely because cheetahs adjust their spatiotemporal patterns on a fine scale to avoid immediate risks of these larger, more dominant carnivores (Broekhuis et al., 2013; Vanak et al., 2013). We found that cheetahs preferred areas dominated by semiclosed habitat which could explain why cheetahs preferred the wildlife areas despite the very high lion densities (Elliot & Gopalaswamy, 2017). Semiclosed habitat provides concealment, thereby minimizing the possibility of being detected by other predators.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Additionally, recent research has shown that lion numbers do not negatively influence cheetah numbers (Swanson et al., 2014), which is likely because cheetahs adjust their spatiotemporal patterns on a fine scale to avoid immediate risks of these larger, more dominant carnivores (Broekhuis et al., 2013; Vanak et al., 2013). We found that cheetahs preferred areas dominated by semiclosed habitat which could explain why cheetahs preferred the wildlife areas despite the very high lion densities (Elliot & Gopalaswamy, 2017). Semiclosed habitat provides concealment, thereby minimizing the possibility of being detected by other predators.…”
Section: Discussionmentioning
confidence: 81%
“…Under the competition‐avoidance hypothesis we expected that cheetahs would prefer areas outside the wildlife areas to avoid competition with other predators, especially lions as they occur at very high densities inside the wildlife areas (Elliot & Gopalaswamy, 2017). However, our results show a strong preference for wildlife areas and an avoidance of human presence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Maasai Mara has a relatively high density of cheetahs with around 1.28–1.34 adults per 100 km 2 (Broekhuis & Gopalaswamy, 2016) which is why, along with the Serengeti National Park, it is an important stronghold for the global cheetah population (Durant et al., 2017). Other predators that occur at high densities in the Maasai Mara are lions, with a density of 17 individuals (>1 year) per 100 km 2 (Elliot & Gopalaswamy, 2017), and spotted hyaenas, with clan sizes in the Maasai Mara National Reserve ranging from 22 to 126 individuals (Green et al., 2018). …”
Section: Methodsmentioning
confidence: 99%
“…The Maasai Mara in Kenya is an ideal place to conduct this study as the habitat is heterogeneous, ranging from wide open grasslands to Vachellia woodland and riverine forests (Oindo, Skidmore, & De Salvo, 2003). The Maasai Mara also has high densities of cheetahs (Broekhuis & Gopalaswamy, 2016) and other predators, including lions (Elliot & Gopalaswamy, 2017) and spotted hyaenas (Green, Johnson‐Ulrich, Couraud, & Holekamp, 2018), which vary spatially. Partly because of these high densities of predators, the Maasai Mara is a popular tourist destination.…”
Section: Introductionmentioning
confidence: 99%